2018
DOI: 10.1002/chem.201801992
|View full text |Cite
|
Sign up to set email alerts
|

Helicity Control of Supramolecular Gel Fibers Consisting of an Achiral NiII Complex in a Chiral Nematic Solvent

Abstract: The supramolecular chirality of aggregates consisting of achiral trans-bis(salicylaldiminato)Ni complex 1 bearing long alkyl chains can be generated and controlled precisely in a chiral nematic liquid-crystalline (LC) solvent, whereas the complex naturally forms achiral gel fibers in achiral nematic LC solvents and crystals in nonmesogenic solvents. The direction and intensity of the helicity of the gel fibers of 1 in the LC gel state can be adjusted by means of the nature of the helical twisting and the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…These results indicated that the induced chirality of the present TN–LC device can be amplified by doping more AIEgens. [ 23 ] In addition, we found that the TN–LC pretilt angle is strongly dependent on the fabrication process of the alignment layer such as the rubbing counts. [ 24 ] The TN–LC device fabricated from alignment layers with more rubbing counts showed stronger CD and CPL signals (Figure 3C,F and Figure S5, Supporting Information), which well matched with our expectation that the stronger directivity of the alignment films would promote better chiral performance.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the induced chirality of the present TN–LC device can be amplified by doping more AIEgens. [ 23 ] In addition, we found that the TN–LC pretilt angle is strongly dependent on the fabrication process of the alignment layer such as the rubbing counts. [ 24 ] The TN–LC device fabricated from alignment layers with more rubbing counts showed stronger CD and CPL signals (Figure 3C,F and Figure S5, Supporting Information), which well matched with our expectation that the stronger directivity of the alignment films would promote better chiral performance.…”
Section: Resultsmentioning
confidence: 99%
“…Naota and co‐workers demonstrated chirality transfer from solvent (chiral nematic liquid crystals) to achiral solute molecules ( trans ‐bis(salicylaldiminato)nickel(II) complexes) to form supramolecular chiral fibers. [ 107 ] The used achiral coordination complexes usually form achiral supramolecular fibers in achiral nematic‐liquid‐crystalline phases and non‐mesogenic crystals. In contrast, helicity intensity and direction of the supramolecular gel fibers can be controlled in chiral nematic liquid crystals as solvents depending on helical twisting nature and chiral dopant concentrations.…”
Section: Chiral Nanoarchitectonics Of Mesoscopic Materials: Liquid Crmentioning
confidence: 99%
“…(Figure 13). 73 The supramolecular chirality of aggregates made of achiral transbis(salicylaldiminato)Ni II complex having long alkyl chains can be precisely controlled within strong chirality-inductive environment of chiral nematic liquid crystalline phase, while any chirality was not induced in achiral nematic liquid crystalline media. In the former case, direction and intensity in the helicity of the complex aggregates can be regulated by the helical twisting nature and the chiral dopants concentrations.…”
Section: Figure 8 Kinetic Investigation On Molecular Recognition Andmentioning
confidence: 99%